2022
DOI: 10.21733/ibad.1031369
|View full text |Cite
|
Sign up to set email alerts
|

Supervision of Group Counseling Practicum with Multiple Supervision Models: Opinions of Master Students

Abstract: 1-Makale katkı oranı eşittir ancak makalenin dergiye sunumu, takip edilmesi ve sonlandırılması sürecini birinci yazar yapmıştır. 2-Makalenin yazarları arasında çıkar çatışması bulunmamaktadır. 3-Bu makalede araştırma ve yayın etiğine uyulmuştur. 4-Araştırmamızın verileri 2020 yılından önce toplanmıştır. Bu yüzden etik kurul izni alınamamıştır.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…This finding obtained as a result of the research supports the results of previous research in the literature. As a result of the research conducted by Yıldırım- Kurtuluş et al (2022), it was concluded that peer supervisors see the convenience of establishing comfortable and friendly relationships and their supportive positions as an advantage. Additionally, Güldal et al (2022) examined the effect of online group peer supervision on the burnout levels of psychological counselors and revealed that peer supervision helps provide a positive group environment.…”
Section: Discussionmentioning
confidence: 99%
“…This finding obtained as a result of the research supports the results of previous research in the literature. As a result of the research conducted by Yıldırım- Kurtuluş et al (2022), it was concluded that peer supervisors see the convenience of establishing comfortable and friendly relationships and their supportive positions as an advantage. Additionally, Güldal et al (2022) examined the effect of online group peer supervision on the burnout levels of psychological counselors and revealed that peer supervision helps provide a positive group environment.…”
Section: Discussionmentioning
confidence: 99%